The god-human relationship in octavia butler’s “the book of martha” - Achachelooei, E.M.; Leon, C.E. (Universiti Kebangsaan Malaysia Press, 2016)
This article explores the relationship between God and a posthuman representative of humanity in Octavia Butler’s “The Book of Martha” (2005). Using Daphne Hampson’s feminist post-Biblical ideas, the article argues that the story, as a sample of science fiction, exposes a posthumanist perspective where existence and subjectivity of human kind is defined based on a mutual, non-hierarchical relationship between human being and God. The article aims to explore the capacity of the story to embody a positive standpoint of science fiction towards the transformation of the human. This article suggests that “The Book of Martha,” reflecting this transformation together with an unothered perspective of the God-human relationship, illustrates the potential for a more humanitarian life on Earth. The relationship is investigated through an unorthodox theological perspective that confronts Christian norms, particularly the norms dealing with what is considered as true femininity. In this way, the story describes a fictional space in which the Christian concept of human as a fallen, condemned, and passive object before a ubiquitous Almighty is substituted with a non-Christian active concept of the human entity. This active representation is based on the recognition of a posthuman agency which is free from surrender to divine power. “The Book of Martha” is about the gradual awakening of a black woman who, in interaction with God as the source of goodness, becomes aware for the need to redefine an authentic sense of self beyond that of an obedient servant before a masculinized God. This article explores this awakening.